Al-La'ibu yabda'u, al-mahārātu tataṭawwaru: at-tamyīzu baina an-niqāṭ al-'Arabiyyah fī taqyīmi mahārati al-kitābah lad : Game On, Skills Up: Differentiated Gamification of Arabic Points in Evaluating the Writing Skills - Naqi’ah; Nur Diana Arifah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Limited vocabulary, grammatical constraints, and a uniform traditional assessment system often hamper Arabic writing skills. This study aims to analyze improvements in student learning outcomes and motivation through the application of “Arab Point Games,” an assessment innovation that integrates gamification with differentiated instruction. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model in two cycles. The research subjects involved 33 students of class X-B at MAN 1 Pamekasan in the 2025/2026 academic year. Research data were collected through observation, writing skills tests, and reflective notes, which were validated by experts and tested for reliability through triangulation. Quantitative analysis showed the intervention's success, based on a minimum increase of 10 points in the score, a classical completion rate of 85%, and a learning motivation rate of 80%. The results showed a significant improvement in students' writing skills. The average score increased from 23.94 in the pre-action stage to 28.00 in Cycle I, and reached 44.39 in Cycle II. Cumulatively, there was an average increase of 20.45 points with a percentage increase of 85.4%. In addition to cognitive achievements, the data show an affective transformation in which students began to dare to take on high-level challenges, reduced linguistic anxiety, and increased active participation, exceeding the 80% success indicator. These findings prove that the “Arab Point Games” intervention is effective in accommodating differences in student learning speeds through an adaptive assessment system. This study contributes theoretically by shifting the paradigm from Assessment of Learning to a more inclusive Assessment as Learning. In practice, this model offers educators a solution for creating an Arabic-language learning ecosystem that is responsive to individual diversity. Keywords: Arab Point Games, Differentiated Learning, Gamification, Writing Skills.